Sulodexide for Secondary Prevention of Recurrent Venous Thromboembolism: A Systematic Review and Meta-Analysis - Jiang, Qing-Jun; Bai, Jun; Jin, Jie; Shi, Jian; Qu, Lefeng (Frontiers in Pharmacology, 2018)
ABSTRACT Background: Patients with venous thromboembolism have high risk of recurrence after discontinuation of anticoagulant treatment. Extended anticoagulation, such as traditional anticoagulants, can reduce the risk of recurrence but is associated with increased risk of hemorrhage. Sulodexide is a natural glycosaminoglycan mixture which can prevent recurrent venous thromboembolism. However, its clinical efficiency and safety still remain controversial. Methods: A systematic search in Medline, EMBASE, Cochrane Library, Web of Science and bibliographies of retrieved articles was performed. Prospective controlled studies reporting the efficacy and safety of sulodexide on the secondary prevention of recurrent venous thromboembolism were included. Two reviewers independently extracted the following data: first author, year of publication, study design, characteristics of patients, data of interventions, doses of sulodexide, overall duration of drug administration, time of follow-up, efficacy and safety outcomes, adverse effects, and the quality of the included studies. The primary efficacy outcomes were recurrent deep vein thrombosis (DVT) or pulmonary embolism. The secondary efficacy outcomes included distal or superficial vein thrombosis and nonfatal or fatal myocardial infarction, stroke, and acute ischemia of the lower limbs. Safety outcome was possible hemorrhagic episodes. Results: Four studies involving 1461 patients were enrolled in this study. Meta-analysis showed that sulodexide significantly reduced the recurrent venous thromboembolism (RR 0.51, 95 % CI [0.35, 0.74], P=0.0004) and superficial vein thrombosis in the sulodexide group (RR 0.41, 95 % CI [0.22, 0.76], P=0.005). The safety of sulodexide was also reliable. The rate of bleeding was 0.28% in the sulodexide group and 1.60% in the control group, and design of study did not influence these results. Conclusions: Sulodexide could significantly reduce the recurrence of VTE after discontinuation of anticoagulation treatment as compared with placebo.